Conflict and legitimacy in modern democratic societies - Laufer, Romain (Javnost (Ljubljana), 2005)
The notion of "diplomatic attitude" in rhetoric as defined by Chaim Perelman may be associated with sophistry. However, such a bias raises the more fundamental question of a possible link between diplomatic rhetoric and sophistic, or even sophistry. Could such a link be theorised to help understand international relations? In other words, does the notion of a "sophistic rhetoric" enable us to characterise the rhetorical shape of international relations today?
Keywords: mednarodni odnosi; communication; komuniciranje; politične komunikacije; diplomacija; diplomacy; argumentacija; retorika; rhetoric